The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ma16031277
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chloride Diffusion Coefficient in Concrete Modified with Supplementary Cementitious Materials Using Machine Learning Algorithms

Abstract: The chloride diffusion coefficient (Dcl) is one of the most important characteristics of concrete durability. This study aimed to develop a prediction model for the Dcl of concrete incorporating supplemental cementitious material. The datasets of concrete containing supplemental cementitious materials (SCMs) such as tricalcium aluminate (C3A), ground granulated blast furnace slag (GGBFS), and fly ash were used in developing the model. Five machine learning (ML) algorithms including adaptive neuro-fuzzy inferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The smaller the value of these three, the smaller the error and the higher the prediction accuracy, that is, the better the point prediction effect. 13 The evaluation indicators are defined as follows:…”
Section: Model Evaluation Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller the value of these three, the smaller the error and the higher the prediction accuracy, that is, the better the point prediction effect. 13 The evaluation indicators are defined as follows:…”
Section: Model Evaluation Metricsmentioning
confidence: 99%
“…The smaller the value of these three, the smaller the error and the higher the prediction accuracy, that is, the better the point prediction effect. 13 The evaluation indicators are defined as follows: where n is the number of samples, y^i is the predicted value of the i th sample, and yi is the real value of the i th sample.…”
Section: Screening Index Interval Prediction Modelmentioning
confidence: 99%
“…Studies [157][158][159][160][161] have found that a large amount of machine-learning-based work has focused on concrete permeability resistance and the diffusion coefficient. Supervised machine learning approaches, such as SVM, RF, and ANN, are mainly used for chloride permeability and diffusion.…”
Section: Application Of Machine Learning To Chloride Penetrationsmentioning
confidence: 99%